2011
DOI: 10.1158/1078-0432.ccr-10-2159
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of the Combination of Intravenous Reovirus Type 3 Dearing and Gemcitabine in Patients with Advanced Cancer

Abstract: Purpose: This study combined systemic administration of the oncolytic reovirus type 3 Dearing (reovirus) with chemotherapy in human subjects. We aimed to determine the safety and feasibility of combining reovirus administration with gemcitabine and to describe the effects of gemcitabine on the antireoviral immune response.Experimental Design: Patients received reovirus in various doses, initially we dosed for five consecutive days but this was poorly tolerated. We amended the protocol to administer a single do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 20 publications
0
79
0
Order By: Relevance
“…During studies on basic reovirus biology, reovirus was discovered to possess an intrinsic specificity toward cancer cells over normal cells (11)(12)(13)(14)(15)(16)(17). Reovirus shows potent antitumor activity in a wide assortment of in vivo cancer models (18)(19)(20)(21)(22) and is being examined in numerous phase I/II and III human clinical trials (23)(24)(25)(26)(27)(28)(29)(30). All trials currently use the reovirus serotype 3 (T3) Dearing strain in its wild-type form (here referred to as T3wt).…”
mentioning
confidence: 99%
“…During studies on basic reovirus biology, reovirus was discovered to possess an intrinsic specificity toward cancer cells over normal cells (11)(12)(13)(14)(15)(16)(17). Reovirus shows potent antitumor activity in a wide assortment of in vivo cancer models (18)(19)(20)(21)(22) and is being examined in numerous phase I/II and III human clinical trials (23)(24)(25)(26)(27)(28)(29)(30). All trials currently use the reovirus serotype 3 (T3) Dearing strain in its wild-type form (here referred to as T3wt).…”
mentioning
confidence: 99%
“…[73] Through this study, the concluding recommended dose for this particular combination was as follows: reovirus 1×10 10 TCID 50 on day 1 and gemcitabine at 1,000 mg/m 2 on day 1 and day 8 of a 21-day cycle. Of the ten evaluable patients, one had a PR and a minor decrease in tumor size after just four cycles of therapy.…”
Section: Combination Therapy With Reovirus In Clinical Studiesmentioning
confidence: 96%
“…[69,71,78] However, the known toxicities of gemcitabine and reovirus were observed in one trial. [73] Lolkema et al concluded that since gemcitabine appears to have an inhibitory effect on the development of neutralizing antireoviral antibodies (NARAs), a chemotherapeutic regimen in combination with reovirusmay exacerbate reovirus toxicity in the liver and further elevate liver enzyme levels. [73] Key obstacles to reovirus oncotherapy With a total of 32 clinical trials (completed or ongoing) and continued progress in preclinical studies, reovirus therapy is well set to transition from "bench" to "bedside" for the treatment of a multitude of cancers.…”
Section: Combination Therapy With Reovirus In Clinical Studiesmentioning
confidence: 99%
“…Building off of preclinical work testing gemcitabine, the first combination reovirus chemotherapeutic clinical trial tested gemcitabine and REOLYSIN in 16 patients with advanced malignancies including head and neck, breast, cervical, and colorectal cancers (51). Of the 10 evaluable patients, 1 patient with metastatic nasopharyngeal carcinoma had a partial response whereas 6 other patients had stable disease for 4 to 8 treatment cycles.…”
Section: Combination Chemotherapymentioning
confidence: 99%